A Robust and Adaptive Lyapunov-Sliding Mode Control Strategy for Electric Motor Applications - Diaby, Tidiane; Zohdy, Mohamed Ali; Shaout, Adnan (Transactions on Engineering and Computing Sciences, 2025)
This paper presents a robust and adaptive control strategy that integrates Lyapunov-based stability and Discrete Time Sliding Mode Control (DTSMC) for speed tracking, and stability enhancement in electric motors. The proposed approach leverages Lyapunov theory to guarantee system stability by designing a positive definite Lyapunov function, ensuring the convergence of tracking errors under varying operating conditions. Simultaneously, the discrete SMC provides robust disturbance rejection and resilience to parameter variations by maintaining system states on a predefined sliding surface. The combination of these two methods addresses the limitations of conventional controllers, which often lack robustness to uncertainties and Disturbances. The effectiveness of the proposed method is validated through theoretical analysis and simulation results on PMSM model, demonstrating superior tracking performance, under different load conditions and system uncertainties.